PENINGKATAN PERTUMBUHAN DAN PERKEMBANGAN CABAI MERAH (Capsicum annum L) DENGAN SAMBUNG PUCUK (GRAFTING) - Dwijowati Asih Saputri; Aulia Ulmillah; Ovi Prasetya Winandari; Iin Martatin Nova (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
Grafting with cayenne pepper rootstock (Capsicum frutescens L.) and red chili scion (Capsicum annum L) can be used to improve the quality of red chili plants. This study aims to determine the growth and development of red chili plants from shoot grafting. The study was carried out with 3 treatments, namely kontrol (without grafting) (Mo), treatment 1 (X1) fighting with scion from the main stem and treatment 2 (X2) grafting with scion from stem branches. Each treatment was repeated 5 times. The results showed that the highest number of leaves was obtained in the kontrol treatment, the highest number of flowers and fruits in the X2 treatment. It was concluded that shoot grafting in red chili with entries from the first branch resulted in plants with the best growth and development. From the results of this study shoot grafting can be used as a way of cultivating red chiliKeywords: Capsicum annum L.; Grafting, Growth and Development.Â Â